Pengalaman Menjalani Proses Pemulihan Individu dengan Ketergantungan NAPZA dan Gangguan Jiwa - Hasnawati, Saptiah; Susanti, Herni (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2021)
Introduction: Drug abuse is a serious problem in every country. Indonesia is geographically located across two continents that allow illegal drugs to enter. More and more drug users, every year have increased. There is some research on drug cases including research on the process of rehabilitation of individuals with dual diagnosis, namely drug dependence, and mental disorders. Objective: This study aims to explore the experience of undergoing the recovery process of individuals with dual diagnoses: drug dependence and mental disorders. Method: phenomenological qualitative research. Keywords used: mental disorders, drug abuse, and recovery. Results: Obtained as many as 15 participants who met the criteria, with the concepts obtained related to the experience of individuals with dual diagnoses found 5 themes namely manifestations of mental disorders that were perceived as not dominant accompanying, varied experiences in carrying out rehabilitation in dual diagnosis individuals, individual efforts to better, better future expectations, experience in adolescence before undergoing dual diagnosis. Conclusion: experience undergoing the recovery process of individuals with dual diagnoses of drug addiction and mental disorders is a specific condition that requires more complex treatment. so that conditions recover from mental disorders and prevent recurrence of drug use can be achieved by individuals.